Eksploitasi Lingkungan dalam Cerpen Di Seine Meratapi Citarum melalui Pendekatan Ekokritik - Rizal Firmansyah; Turahmat Turahmat (Aksara: Jurnal Bahasa dan Sastra, 2019)
Disasters, pollution, and animal hunting continue to occur unnoticed that humans are part of their lives. The purpose of this study is to explore the form of the study of the short story writer "On the Seine Lamenting Citarum" which has an environmental theme. and analyze the ecocritical elements reflected by the author through a short story, "On the Seine Lamenting Citarum". This study uses a qualitative descriptive method. The approach used is the Garrard ecocritical approach. The data source consists of three short stories, namely, "On the Seine Lamenting Citarum" the author reflects on environmental phenomena which include water pollution. Exploitation of nature which brings casualties. The environmental phenomenon contained in the short story focuses on pollution, settlements, and the earth. http://dx.doi.org/10.23960/aksara/v20i2.pp101-108